Beyond the capital: peripheral modernities and uneven citizenship in contemporary literature from Eastern Indonesia - Sadani (Indonesian Journal of Politics and Literary Studies, 2026)
Background: Contemporary Indonesian literary studies has increasingly addressed nationalism, memory, gender, mobility, and political resistance, yet literature from Eastern Indonesia remains insufficiently theorised as a site where peripheral modernities and uneven citizenship are narratively produced. Objective: This study examines how contemporary literary works set in Papua, Maluku, Nusa Tenggara Timur, Maluku Utara, Sulawesi Tenggara, and Sulawesi Selatan represent modernity, belonging, and citizenship beyond capital-centred national imagination. Method: This study applies qualitative literary analysis to a selected corpus of Eastern Indonesian fiction, supported by postcolonial literary criticism, peripheral modernity, citizenship studies, and narrative counter-cartography. Results: Findings show that peripheral modernity is narrated through fragile roads, maritime routes, schools, markets, borders, commodities, and uneven institutional access rather than through simple absence or developmental delay. Findings also indicate that citizenship appears as an embodied and locally mediated condition shaped by gender, customary authority, bureaucracy, education, violence memory, and community obligation. Implication: Findings further demonstrate that narrative form remaps Indonesia through island memory, village chronotopes, women’s testimony, child focalisation, ritual temporality, and maritime spatiality. Novelty: This study contributes a counter-cartographic framework for reading Eastern Indonesian literature as a critical archive of unequal national belonging.